The influence of positive reflection on attributions, emotions, and self-efficacy - Allen, M. S.; Jones, M. V.; Sheffield, D. (The Sport Psychologist, 2010)
The purpose of this study was to explore the influence of postcompetition positive reflection on attributions, emotions, and self-efficacy. Following a golf putting competition, participants (n = 80) were randomly assigned to either an experimental or control group. In the experimental group participants completed a modified version of the performance evaluation sheet (Holder, 1997). In the control group participants completed the concentration grid exercise (Harris & Harris, 1984). All participants subsequently completed measures of causal attribution, emotion, and self-efficacy. Findings showed that participants in the experimental condition made attributions that were significantly more internal and personally controllable than participants in the control group irrespective of competition outcome. No differences were observed between groups on measures of emotion and self-efficacy. This study suggests that reflecting back on positive elements of performance is a useful strategy for developing desirable attributions in sport performers, but may not necessarily promote self-efficacy or positive emotions.